Information Security Practice and Experience : 15th International Conference, ISPEC 2019, Kuala Lumpur, Malaysia, November 26–28, 2019, Proceedings /: 15th International Conference, ISPEC 2019, Kuala Lumpur, Malaysia, November 26–28, 2019, Proceedings. (2019) - Unknown
No abstract available